How gaming became sexist: a study of UK gaming magazines 1981–1995. - Kirkpatrick, Graeme (Media, Culture & Society, 2017)
Computer gaming was not born sexist but was codified as an exclusively male practice as it peeled itself away from the rest of the burgeoning computer culture in the mid-1980s. This article traces the development of gaming’s gender bias through a discourse analysis of gaming magazines published in the United Kingdom between 1981 and 1995. In their early years (1981–1985), these publications present a milieu that was reflective on gender issues and concerned to include female participants. However, from 1987, the rhetorical framing of computer games, gaming and gamer performance was increasingly gender-exclusive and focused on the re-enforcement of stereotypically masculine values, albeit that much of this discourse had a humorous and ironic inflection. The article presents this as the gender-biased articulation of gaming discourse. Instead of viewing the gendering of computer games as something they inherited from previous kinds of games and activities, the article argues that the political economy of the gaming industry in the second half of the 1980s created specific conditions under which games and gaming were coded as exclusively masculine.